2022
DOI: 10.1007/s12144-022-03822-4
|View full text |Cite
|
Sign up to set email alerts
|

A moderated-mediation analysis of abusive supervision, fear of negative evaluation and psychological distress among Egyptian hotel employees

Abstract: By integrating cognitive appraisal and social exchange theories, this paper examines the linkage of supervisors’ abusive reactions with psychological distress through their subordinates’ fear of negative evaluation. This paper also investigates the moderating role of negative reciprocity. Data were gathered from 412 employees at 15 five-star hotels in Egypt and analyzed using PROCESS 4.0 macro in SPSS (Model 5). The findings revealed that abusive supervision was strongly positively connected with psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…The construct items were reordered as procedural remedies to the data set to eliminate guessing by all the respondents. Furthermore, all items had precise and shortened phrases, and the survey’s introduction included a sentence about not disclosing the respondents’ personal information (Selem et al , 2022b). In this paper, two statistical techniques were applied to address CMB.…”
Section: Methodsmentioning
confidence: 99%
“…The construct items were reordered as procedural remedies to the data set to eliminate guessing by all the respondents. Furthermore, all items had precise and shortened phrases, and the survey’s introduction included a sentence about not disclosing the respondents’ personal information (Selem et al , 2022b). In this paper, two statistical techniques were applied to address CMB.…”
Section: Methodsmentioning
confidence: 99%
“…Low-level interpersonal mistreatment constitutes impoliteness (Selem et al, 2023a). Incivility would be at the lower end of a spectrum of psychological deviance's level or intensity if such a continuum existed (Khan et al, 2023b).…”
Section: Co-worker Incivilitymentioning
confidence: 99%
“…Gender as a potential moderator of incivility stems from research on gender differences in communication styles and conflict resolution strategies (Selem et al, 2023a). Gender may influence the perception and expression of incivility in workplace interactions, according to these studies.…”
Section: Promotion Focus and Gender As Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple researchers have noted that FNE is the leading cause of social anxiety in adolescents that impacts their SE (Li et al, 2023;Naidu et al, 2023;Niu et al, 2023). Selem et al (2023) defined FNE as dread about others' evaluation, anxiety regarding the possibility of an opposing decision, prevention of situations involving evaluations, and the expectation of being negatively evaluated (Selem et al, 2023). Previous research has demonstrated that individuals with a high FNE are more stressed than those with a low FNE (Akkuş, 2023).…”
Section: Introductionmentioning
confidence: 99%